Lactate and SOFA Score as Predictors of Sepsis Mortality: A Retrospective Observational Study - Hardianti, Anugerah; Ahsan, Ahsan; Kristianto, Heri; Lande, Hasriadi (Journal of Applied Nursing and Health, 2025)
Background: Managing sepsis in the emergency room presents a significant challenge, as the condition is often difficult to recognize, leading to a delay in identification and diagnosis, frequently only after the patient has reached a critical state. This study aims to analyze the correlation between lactate levels and Sequential Organ Failure Assessment (SOFA) scores with mortality risk in patients with sepsis: a retrospective study conducted in the emergency room of Dr. Wahidin Sudirohusodo Hospital, Makassar. This study follows the STROBE guidelines for observational research. Methods: This study employs a quantitative, analytical observational design with a retrospective approach. The sample consists of 321 sepsis patients diagnosed with sepsis or presenting comorbidities associated with sepsis in the Emergency Room of Dr. Wahidin Sudirohusodo Hospital, Makassar. The sample size was determined using the Slovin formula. Purposive sampling was employed as the sampling technique, while data analysis included descriptive statistics, chi-square tests, and binary logistic regression. Results: Elevated lactate levels and SOFA scores were significantly associated with increased mortality (p <0.05). Lactate levels demonstrated an odds ratio (OR) of 5.329, indicating that patients with low lactate levels were 5.3 times more likely to survive than those with high lactate levels. The SOFA score produced an OR of 10.058, suggesting that patients with lower SOFA scores had a 10.1 times greater chance of survival compared to those with higher scores. Lactate level was identified as the primary predictor of mortality. Conclusion: The results of this study indicate a significant correlation between blood lactate levels and SOFA scores with sepsis-related mortality in the Emergency Department (ED). Among these two parameters, blood lactate emerged as the most dominant predictor. These results underscore the importance of implementing early detection tools for sepsis, such as lactate testing and simplified SOFA assessments, as part of routine triage workflows, particularly at Dr. Wahidin Sudirohusodo General Hospital in Makassar.